Curricular reform of the study plan of Bachelor in English Teaching and its correspondence to students’ needs, Foreign Language Department, University of El Salvador year, 2014. - Ayala Chavarría, Roxana Patricia
Education is defined as the process by acquiring new knowledge and developing new skills in order to get ready to face the society needs; besides that, education is very important because it allows a country to grow up in different areas of human life. In El Salvador, educational services are offered from early education to higher education, in which they develop a curricular plan provided by the Ministry of Education, these curricular plans, according to the law, must be updated in order to fulfill the expectations of the new society requirements. The University of El Salvador is one of the highest educational institutions, best known as the “Alma Mater” since the quality of its education is one of the highest in the country; however, some of the majors in this institution have not updated their curricular plans. This research is mainly focused on the Foreign Language Department of this university, especially in the Bachelor in English Language Teaching; this major is still working with the curricular reform of 1992 and according to the General Law of Higher Education, university plans must be updated every five years. As a matter of fact, updating a curriculum is important because the society is changing and institutions must get along with those changes. According to the opinion of some experts, there are many elements to be taken into account when updating a curriculum. This research has been developed by taking a population from different educational institutions (bilingual schools, English academies, universities) from the metropolitan area. These institutions provided information about the main requirements they seek in a good professional to get hired. Also, they give their opinion about the professionals that are graduating with this plan. On the other hand, students’ opinion is taken into account by providing information about which of their real needs in order to be added in a possible new curriculum in the major. Once the information is gathered, a diagnosis is presented, it shows the possible changes the curriculum may have and how it can be improved in order to prepare better professionals.